2016
DOI: 10.26719/2016.22.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the VITEK 2 system for a rapid and direct identification and susceptibility testing of Gram-negative rods and Gram-positive cocci in blood samples

Abstract: The performance of the VITEK ® 2 system for direct rapid identification and antimicrobial susceptibility testing of the bacteria responsible for blood infections was determined. The isolates studied included 166 Gram-negative rods and 74 Gram-positive cocci from inpatients. Specially treated monomicrobial samples from positive blood culture bottles were directly inoculated into the VITEK 2 system and the results were compared with those from cards inoculated with standardized bacterial suspensions. Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…The Vitek 2 system can identify gram-negative rods within 4 h. This system has shown to be an accurate, easy, and rapid tool for the identification of K. pneumoniae isolates [24]. In our study, the Vitek 2 system demonstrated a similar rate of accuracy in the identification of Klebsiella and identified the isolates to the species level.…”
Section: Vol 8 Nosupporting
confidence: 61%
“…The Vitek 2 system can identify gram-negative rods within 4 h. This system has shown to be an accurate, easy, and rapid tool for the identification of K. pneumoniae isolates [24]. In our study, the Vitek 2 system demonstrated a similar rate of accuracy in the identification of Klebsiella and identified the isolates to the species level.…”
Section: Vol 8 Nosupporting
confidence: 61%
“…Bacterial isolates were identified based on cultural and biochemical criteria. The method followed was adapted from a previous study that reported that VITEK2 cards inoculated with fluids sampled directly from culture bottles are suitable for speedy identification and susceptibility testing [15]. A sterile swab or applicator stick was used to transfer a sufficient number of colonies of a pure culture in 3.0 mL of sterile saline (0.45% NaCl, pH 4.5-7.0) in a 12×75 mm clear plastic (polystyrene) test tube.…”
Section: Methodsmentioning
confidence: 99%
“…A sterile swab or applicator stick was used to transfer a sufficient number of colonies of a pure culture in 3.0 mL of sterile saline (0.45% NaCl, pH 4.5-7.0) in a 12×75 mm clear plastic (polystyrene) test tube. The turbidity was adjusted to 0.50-0.63 Mf and measured using a turbidity meter known as DensiChek [15]. Results were read overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Marcy l’Etoile, France) used in the present study is an automated system for identification and antimicrobial susceptibility testing after a standardized inoculum has been loaded into the system. The results are available within 3 h for identification and 18 h for susceptibility testing [ 15 ]. However, the crucial need for speeding up the process of identification and antimicrobial susceptibility of the positive blood cultures lead to more recent advances that allow more rapid identification within 1 h. The BioFire FilmArray blood culture ID (BCID2; bioMérieuxm Marcy l’Etoile, France) is a highly multiplexed PCR kit that identifies 33 species, including 28 bacterial species and five Candida species.…”
Section: Introductionmentioning
confidence: 99%